2020
DOI: 10.3390/en13082079
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Wellbeing and Quality of Life: A Scientific Literature Review on Thermal Comfort

Abstract: While indoor comfort represents a widely investigated research topic with relation to sustainable development and energy-demand reduction in the built environment, outdoor comfort remains an open field of study, especially with reference to the impacts of climate change and the quality of life for inhabitants, particularly in urban contexts. Despite the relevant efforts spent in the last few decades to advance the understanding of phenomena and the knowledge in this specific field, which obtained much evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 194 publications
(154 reference statements)
0
6
0
1
Order By: Relevance
“…Because of this, these LCZs have conditions to have higher temperatures compared to other LCZs and rural areas. As cities expand, contributing to the intensification of Urban Heat Island effects (Huang et al 2017 ), it is in the most densely built urban areas where these effects are most pronounced (Antonini et al 2020 ; Lin et al 2017 ; Lopes et al 2013 ; Zheng et al 2023 ). As Zheng et al ( 2023 ) notes, UHII conditions are closely linked to urban morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, these LCZs have conditions to have higher temperatures compared to other LCZs and rural areas. As cities expand, contributing to the intensification of Urban Heat Island effects (Huang et al 2017 ), it is in the most densely built urban areas where these effects are most pronounced (Antonini et al 2020 ; Lin et al 2017 ; Lopes et al 2013 ; Zheng et al 2023 ). As Zheng et al ( 2023 ) notes, UHII conditions are closely linked to urban morphology.…”
Section: Discussionmentioning
confidence: 99%
“…These extreme temperatures and induced thermal stress pose threats to human well-being and health (Foshag et al 2020 ). As cities continue to grow, it is predicted that the Urban Heat Island (UHI) will intensify, thereby jeopardizing human thermal comfort (Antonini et al 2020 ; Elnabawi and Hamza 2020 ; Huang et al 2017 ; Lin et al 2017 ). Oliveira et al, ( 2021b ) found that in Lisbon the UHI is not intensified by extreme heat phenomena such as heatwaves.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of life in urban environments [1] is closely related to the above-mentioned elements and their possible combinations. Among them, some are directly measurable, such as climate and the physical and dimensional characteristics of architectural settlements; others are indirectly measurable, such as crowding, traffic and pollution and, finally, others cannot be measured, i.e., people's affection and care for certain city areas.…”
Section: Introductionmentioning
confidence: 99%
“…i-Tree Canopy was recently applied in the scientific literature to quantify green cover and its economic benefits [25][26][27][28][29][30][31][32][33], while there are no studies applying such a tool in Lecce. ENVI-met was successfully employed in studies analyzing the effects of vegetation on microclimate and thermal comfort in the urban environment, where it was thoroughly described [34][35][36][37][38][39][40]; it was also employed for an investigation of air quality, focusing on air pollutant deposition and dispersion in several studies [41][42][43][44][45][46][47][48][49], which mostly found a satisfactory agreement with observations and concluded that, although it is not a very sophisticated model, it provides sufficient functions for establishing small-scale pollutant distribution for studies of urban greening in near-road environments. Specifically, the model was only applied to evaluate the microclimate in some districts of Lecce [50][51][52], while, to our knowledge, there are no papers applying the model to evaluate the impact of urban greening on the dispersion of air pollutants in the city of Lecce.…”
Section: Introductionmentioning
confidence: 99%